Accelerating Open RAN Research Through an Enterprise-scale 5G Testbed - Bahl, Victor; Balkwill, Matthew; Foukas, Xenofon; Kalia, Anuj; Kim, Daehyeok; Kotaru, Manikanta; Lai, Zhihua; Mehrotra, Sanjeev; Radunovic, Bozidar; Saroiu, Stefan; Settle, Connor; Verma, Ankit; et al. (Annual International Conference on Mobile Computing and Networking (MobiCom ’23), 2023)
Open RAN is an emerging paradigm in mobile networks where the Radio Access Network (RAN) functions are disaggregated and virtualized on commodity servers. Despite the importance of Open RAN research, existing platforms often lack the fidelity and stability required to address a wide range of research problems. In response to this limitation, we have developed an enterprise-scale Open RAN testbed aimed at conducting state-of-the-art research in key areas that have received limited attention due to the lack of suitable platforms. In this poster, we provide an overview of the testbed we have created and examples of the research it has enabled, with the hope of catalyzing future open RAN research and innovation.
(authors in alphabetical order)